PENGARUH ETIKA BISNIS ISLAM DALAM MENINGKATKAN MINAT BELI KONSUMEN DI PASAR TANJUNG PURA - Halwani Aswida; Diyan Yusri; Anjur Perkasa Alam (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
The success of a business requires tips to attract consumers. One of them is business ethics, business ethics is an important part that must be owned by a businessman, because ethics is seen as a requirement in making decisions in business matters. Business ethics include fairness in weighing, honestly explaining the condition of the goods, as well as ihsan/being friendly in serving consumers. This study aims to determine 1). How much influence the application of the concept of justice has on consumer buying interest, 2). The influence of the application of the concept of honesty and 3). Great influence on the application of the concept of ihsan. This type of research is an explanatory research with a quantitative approach. This study uses multiple linear regression analysis, the method of collecting with questionnaires and observation and data analysis methods, namely classical assumption test and hypothesis testing. The result obtained is that the variable of justice has an effect of 2,032, meaning that there is a positive or unidirectional relationship between the variable of justice and consumer buying interest. The honesty variable has an effect of -0.513, which means that there is a negative or non-unidirectional relationship between the honesty variable and consumer buying interest. The ihsan/generous variable has an effect of 3.175, meaning that there is a positive or unidirectional relationship between the ihsan/generous variable and consumer buying interest.